Coworker Exchange, Leader-Member Exchange, and Work Attitudes:P A Study of Coworker Dyads - Wikaningrum, Tri (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2007)
The purpose of this study is to examine how leader-member exchange (LMX) similarity might affect exchange quality between coworkers. This research also investigates the relationships of LMX and CWX (coworker exchange) to employeesâ organizational commitment and job satisfaction. Each respondent from 76 nurses at three hospitals in Semarang were asked to rate the quality of the relationship he/she had with his/her supervisor, resulting in 76 LMX ratings. They were also asked to rate the quality of their relationships with each of their coworkers. A dyad was created where we had complete information on two employees rating one another. Once paired, a total of 146 dyads with complete LMX, CWX, and work attitude data were acquired. The results of this research indicate that the interaction between two coworkersâ LMX scores predicts CWX quality for the coworker dyad. After controlling for CWX, LMX quality is positively related to job satisfaction, but not to organizational commitment. Furthermore, after controlling for LMX, a greater diversity in a workerâs CWX relationship is negatively associated to his/her organizational commitment, but not to his/her job satisfaction. The interaction of CWX quality and CWX diversity, however, does not predict work attitude.